Students’ Motivation, Learning Strategies, and Math Performance in the Modular Distance Learning During the COVID-19 Pandemic - Eldee R. Balolong; Melissa R. Gerzon; Stephen J. Manilag; Emerson D. Peteros; Jonathan O. Etcuban (REDIMAT)
This study assessed the motivation, learning strategies, and academic performance of Grade 11 modular-based students in General Mathematics in identified secondary schools as a basis for a proposed performance enhancement plan. There were 624 Grade 11 students across three public senior high schools in Cebu who were determined using stratified random sampling. The respondents were asked to answer the adopted survey questionnaire on “Strategies for Learning Questionnaire (MSLQ)” by Pintrich et al. (1991) to assess the learners' motivational levels and learning strategies while their second quarter grades were used as a datum reference to evaluate the strength of correlation. Data gathered were statistically treated using frequency, percentage, weighted mean, rank, and Chi-square test of independence. Results revealed that the respondents had motivational levels classified as moderately motivated; meanwhile, under the learning strategies, the respondents agreed on the methods employed towards learning General Mathematics. The overall general mathematics average among 624 students is 88.44 with a standard deviation of 5.76, indicating that they had very satisfactory performance in General Mathematics. Thus, a performance enhancement plan was crafted to improve both motivational levels and learning strategies.